Capacity constrained price competition and entry deterrence in heterogeneous product markets - Norbert Schulz (University of Würzburg, Department of Economics, 1999)
In this paper three issues are pursued. First, a model of capacity constrained price competition is suggested. The basic feature of this model is that a pure strategy equilibrium exists for all price subgames. Second, this permits Cournot outcomes in heterogeneous markets to be interpreted as the unique subgame perfect equilibrium of a two stage game where firms simultaneously set capacities first and then prices. Third, the capacity constrained price competition game can be used to extend the entry deterrence models of the Dixit-Stackelberg type in order to analyze the effect of heterogeneity and development of demand. The results support the view that entry deterrence should be a rare event for growing dynamic markets with ample opportunities of product differentiation.
Keywords: 330; Preiswettbewerb; Produktionskapazität; Duopol; Markteintritt; Theorie